Feasibility of a quality-improvement program based on routinely collected health outcomes in Dutch primary care physical therapist practice: a mixed-methods study - LSF Smeekens; AC Verburg; MJM Maas; R van Heerde; A van Kerkhof; PJ van der Wees (BMC, 2024)
Abstract Background This study evaluates the feasibility of a nine-month advanced quality-improvement program aimed at enhancing the quality of care provided by primary care physical therapists in the Netherlands. The evaluation is based on routinely collected health outcomes of patients with nonspecific low back pain, assessing three feasibility domains: (1) appropriateness, feasibility, and acceptability for quality-improvement purposes; (2) impact on clinical performance; and (3) impact on learning and behavioral change. Methods A mixed-methods quality-improvement study using a concurrent triangulation design was conducted in primary care physical therapist practice. Feedback reports on the processes and outcomes of care, peer assessment, and self-assessment were used in a Plan-Do-Study-Act cycle based on self-selected goals. The program's appropriateness, feasibility, and acceptability, as well as the impact on clinical performance, were evaluated using the Intervention Appropriate Measure, Feasibility Intervention Measure, Acceptability Intervention Measure (for these three measure, possible scores range from 4 to 20), and with a self-assessment of clinical performance (scored 0-10), respectively. The impact on learning and behavioral change was evaluated qualitatively with a directed content analysis. Results Ten physical therapists from two practices participated in this study. They rated the program with a mean of 16.5 (SD 1.9) for appropriateness, 17.1 (SD 2.2) for feasibility, and 16.4 (SD 1.5) for acceptability. Participants gave their development in clinical performance a mean score of 6.7 (SD 1.8). Participants became aware of the potential value of using outcome data and gained insight into their own routines and motivations. They changed their data collection routines, implemented data in their routine practice, and explored the impact on their clinical behavior. Conclusions This explorative study demonstrated that a quality-improvement program, using health outcomes from a national registry, is judged to be feasible. Impact statement This study provides preliminary evidence on how physical therapists may use health outcomes to improve their quality, which can be further used in initiatives to improve outcome-based care in primary physical therapy.